2000
DOI: 10.1080/03014223.2000.9518207
|View full text |Cite
|
Sign up to set email alerts
|

Density dependent prey‐feeding time ofStethorus bifidus(Coleoptera: Coccinellidae) onTetranychus lintearius(Acari: Tetranychidae)

Abstract: The gorse spider mite, Tetranychus lintearius, a biological control agent introduced into New Zealand to control gorse, is often attacked by the endemic coccinellid, Stethorus bifidus. Predation by S. bifidus has been suggested as a reason why T. lintearius colonies collapse. For S. bifidus predation to regulate T. lintearius populations, at least one component of its numerical or functional response must result in an increased proportion of mites being killed as mite density increases. Laboratory experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Stethorus punctum continued to feed even when satiated with high prey densities and continued to pierce mites, initiate feeding, but then subsequently abandon the prey with minimal extraction of bodily fluids in a classic Type 3 response. This type of response has been observed in other systems as well (Hull et al 1977a;Haji-Zadeh et al, 1993;Peterson et al, 2000). Types 1 and 2 functional responses have been observed in other Stethorus spp.…”
Section: Developmental and Prey Consumption Ratesmentioning
confidence: 68%
See 1 more Smart Citation
“…Stethorus punctum continued to feed even when satiated with high prey densities and continued to pierce mites, initiate feeding, but then subsequently abandon the prey with minimal extraction of bodily fluids in a classic Type 3 response. This type of response has been observed in other systems as well (Hull et al 1977a;Haji-Zadeh et al, 1993;Peterson et al, 2000). Types 1 and 2 functional responses have been observed in other Stethorus spp.…”
Section: Developmental and Prey Consumption Ratesmentioning
confidence: 68%
“…In New Zealand, the native S. bifidus and less commonly the exotic P. persimilis suppress gorse spider mite populations to the extent that ''after several years populations decline rapidly, and never outbreak again" (Hill et al, 2000). Peterson et al (2000) found that S. bifidis can regulate T. lintearius, based on its functional response in laboratory arenas.…”
Section: Inhibition Of Gorse Biocontrolmentioning
confidence: 99%
“…Particularly in the latter case, this can increase the ' killing power ' of the predator. The handling time of adults of the mite -feeding Stethorus bifi dus , for example, decreases at increased densities of Tetranychus lintearius as the predator extracts less of the killed prey contents (Peterson et al 2000 ;Fig. 5.30 ).…”
Section: Temperature ( °C) Predator Mean Number Eaten ( ±Sd) Estimatementioning
confidence: 99%
“…(2000); i Syrett (1989); j Roberts & Sutherland (1989); k Hill (1989); l Shea & Kelly (2004); m Gourlay (2004); n Paynter et al. (2008b); o Peterson et al. (2000); p Paynter et al (2006).…”
Section: Resultsmentioning
confidence: 99%